No effect of meal intake on physiological or perceptual responses to self-selected high intensity interval exercise (HIIE) - Todd A. Astorino; Sarah Sherrick; Monique MariscalI; Vianney Camarillo Jimenez; Kelli Stetson; Daniel Courtney (Termedia Publishing House, 2019)
The present study examined the effect of meal intake on physiological and psychological indices during self-selected high intensity interval exercise (HIIE). Seventeen active men and women (age = 26.4 ± 5.8 yr) completed ramp cycle ergometry to determine maximal oxygen uptake and peak power output. On two subsequent days, they performed a session of self-selected HIIE consisting of ten 1 min bouts separated by 1 min recovery in the fed or fasted state, whose order was randomized. Meal intake consisted of a banana and a Zone™ bar containing 315 kcal, which were ingested 2 h pre-exercise, and the fasted state required no food for > 12 h pre-exercise. Participants ingested an identical meal the evening before each session. Heart rate (HR), oxygen uptake (VO2), blood glucose and blood lactate concentration, rating of perceived exertion (RPE), affect, and enjoyment were measured during exercise. Irrespective of fed state, both bouts elicited intensities equal to 94%HRmax which represents HIIE. Our results showed no difference in HR (174.0 ± 13.5 vs. 173.2 ± 12.9 b/min in fed and fasted state, p = 0.17), VO2 (2.43 ± 0.54 vs. 2.40 ± 0.52 L/min in fed and fasted state, p = 0.14), RPE (p = 0.44), affect (p = 0.79), or enjoyment (103 ± 14 vs. 101 ± 13, p = 0.77) between the fed and fasted state. Despite its high reliance on carbohydrate, performance and perception of low-volume HIIE are not altered by ingestion of a meal before exercise.